2007
DOI: 10.1002/hec.1299
|View full text |Cite
|
Sign up to set email alerts
|

Cost inefficiency and hospital health outcomes

Abstract: This study explores the association between cost inefficiency and health outcomes in a national sample of acute-care hospitals in the US over the period 1999-2001, with health outcomes being measured by both mortality and complications rates. The empirical analysis examines health outcomes as a function of cost inefficiency and other determinants of outcomes, using stochastic frontier analysis to obtain hospital cost inefficiency scores. The results showed no systematic pattern of association between cost inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…Eggleston and Shen (2011) find that the mortality rate for elderly heart attack patients is higher in for-profit hospitals, because they have more restrictive budget constraints. McKay and Deily (2008) also suggest that reductions in costs are associated with adverse consequences on health outcomes. In addition, not-for-profit hospitals enjoy tax exemptions.…”
Section: Discussionmentioning
confidence: 99%
“…Eggleston and Shen (2011) find that the mortality rate for elderly heart attack patients is higher in for-profit hospitals, because they have more restrictive budget constraints. McKay and Deily (2008) also suggest that reductions in costs are associated with adverse consequences on health outcomes. In addition, not-for-profit hospitals enjoy tax exemptions.…”
Section: Discussionmentioning
confidence: 99%
“…Following the previous literature, we assume that a hospital chooses a set of inputs that will minimize the costs of production given a certain level of output [30]. The production process, described by a production function, converts inputs, such as medical and non-medical personnel, buildings, and equipment, into a given level of output, such as the number of discharges and outpatient visits.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Using SFA, several studies investigated the relationship between inefficiency and several measures of hospital outcomes [25]. Deily and McKay (2006) and McKay and Deily (2008) introduced an inefficiency term as a covariate to explain hospital health outcomes and found a positive relationship between cost-inefficiency and mortality rate in hospitals located in Florida, but not for the entire nation [29,30]. Deily, McKay, and Dorner (2000) found that high costinefficiency was strongly associated with a greater likelihood of non-government-owned hospital closure; while Frech and Mobley (2000) reported that cost-inefficiency was negatively correlated with future growth [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…5,21 Fewer studies have examined the empirical relationship between costs and quality of care. [22][23][24][25][26][27][28] These studies shed light on whether higher costs are, on average, associated with better quality of care and whether hospitals' efforts to reduce costs may have adverse effects on quality. In each of these studies, the measures of quality and costs are averaged across patients within each hospital, which precludes consideration of the relationship between costs and quality for specific hospitals.…”
Section: The Correlation Between Outcomes and Costsmentioning
confidence: 99%